Kritična sporazumevalna zmožnost - osrednji koncept sodobnega pouka prvega jezika - Vogel, Jerica (Jezik in slovstvo, 2021)
Since 2008, critical communicative competence has been defined as one of the central goals of teaching Slovenian as the first language, but it has not yet been sufficiently implemented in teaching practice. As one of the reasons seems to be the lack of a clear definition of this concept in Slovenian language didactics, the paper tries to define critical communicative competence. Based on the concept of key competencies and the characteristics of critical thinking, critical communicative competence is represented as a complex competence, realised as the intertwining of cognitive, linguistic and contextual competencies. It requires the speaker to be aware of the relationship between language and culture, to be capable of metacognition, and to accept ethical and social responsibility.
Keywords: cognitive competencies; contextual competencies; critical communicative competence; first language; first language teaching; jezikovna zmožnost; key competence; ključne zmožnosti; kognitivna zmožnost; kontekstualna zmožnost; kritična sporazumevalna zmožnost; linguistic competencies; pouk prvega jezika; prvi jezik; Slovenian; slovenščina